1997
DOI: 10.1007/s004380050530
|View full text |Cite
|
Sign up to set email alerts
|

SUR1 (CSG1 / BCL21), a gene necessary for growth of Saccharomyces cerevisiae in the presence of high Ca2+ concentrations at 37° C, is required for mannosylation of inositolphosphorylceramide

Abstract: Saccharomyces cerevisiae cells require two genes, CSG1/SUR1 and CSG2, for growth in 50 mM Ca2+, but not 50 mM Sr2+. CSG2 was previously shown to be required for the mannosylation of inositolphosphorylceramide (IPC) to form mannosylinositolphosphorylceramide (MIPC). Here we demonstrate that SUR1/CSG1 is both genetically and biochemically related to CSG2. Like CSG2, SUR1/CSG1 is required for IPC mannosylation. A 93-amino acid stretch of Csg1p shows 29% identity with the alpha-1, 6-mannosyltransferase encoded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 30 publications
5
146
0
Order By: Relevance
“…Mass spectrometry confirmed these results and showed that the biosynthetic pathway was interrupted upstream between IPC and MIPC. Despite slight differences between S. cerevisiae and C. albicans phytosphingosine and fatty acid chains already observed with another C. albicans strain, these results confirm that the C. albicans gene MIT1, like its homologue SUR1 in S. cerevisiae (18), is responsible for the addition of mannose to inositol of IPCs. As expected, inactivation of MIT1 prevented further addition of inositol phosphate leading to the synthesis of M(IP) 2 C. This inactivation also prevented the addition of mannose phosphate, the first step in the extensive mannosylation of sphingolipids deduced from complete elucidation of the…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Mass spectrometry confirmed these results and showed that the biosynthetic pathway was interrupted upstream between IPC and MIPC. Despite slight differences between S. cerevisiae and C. albicans phytosphingosine and fatty acid chains already observed with another C. albicans strain, these results confirm that the C. albicans gene MIT1, like its homologue SUR1 in S. cerevisiae (18), is responsible for the addition of mannose to inositol of IPCs. As expected, inactivation of MIT1 prevented further addition of inositol phosphate leading to the synthesis of M(IP) 2 C. This inactivation also prevented the addition of mannose phosphate, the first step in the extensive mannosylation of sphingolipids deduced from complete elucidation of the…”
Section: Discussionsupporting
confidence: 70%
“…Morphogenesis was not affected by the deletion, including the yeast-to-hyphal transition considered to be a pathogenic trait of C. albicans. However, as observed for sur1⌬ in S. cerevisiae (18), the mutant was more sensitive to calcium. This result, suggesting a plasma membrane or cell wall defect, was confirmed by increased sensitivity of the strain to SDS.…”
Section: Fig 4 Mit1 Deletion Does Not Affect Cell Morphogenesismentioning
confidence: 82%
See 2 more Smart Citations
“…This reaction requires two genes, SUR1 24 and CSG2. 303 IPC accumulates in the absence of either gene.…”
Section: Sphingolipid Biosynthetic Pathway: Genes Enzymes and Phenotmentioning
confidence: 99%